Institutional change in the natural sciences : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Business Studies in Management at Massey University, Palmerston North, New Zealand / - Dickson, Andrew Gordon (Massey University, 2007)
This thesis investigates the Allan Wilson Centre for Molecular Ecology and Evolution, a Centre of Research Excellence financed by the New Zealand Government's CoRE fund, which was established in 2001. The CoRE fund represented a change from traditional science funding in New Zealand. Its aim was to make use of existing networks of scientists, from several institutions and disciplines, to form new 'Centres of Research Excellence', independent from any existing institution, but made up of members who remained in their existing positions. The aim of this thesis is to investigate whether the formation of the Allan Wilson Centre has made a difference to the way its members carry out their science and, if so, how. To do this, an actor-network approach is used to analyse the various 'modes of ordering' the Centre, to make sense of the networks represented by it. The results show an interesting shift in the way that science is carried out in the Allan Wilson Centre in contrast to the pre-Centre form. Although the focus of the Centre remains firmly on the science they do, they now also interact regularly with the discourse of management in order to better 'do' and 'encourage' their science, creating new successes but also new tensions. The importance of this thesis is two-fold. First, it provides a mechanism through which to 'hear' the voice of the Allan Wilson Centre and its members; and second, it provides a means through which science policy makers can see how this particular policy mechanism may have changed the process of science.
Keywords: New Zealand; Science and state; Endowment of research; Science -- Research grants; Allan Wilson Centre for Molecular Ecology and Evolution